Problems of increasing the efficiency of tax administration - Ермекбаева, Б.; Блембаева, A. (Journal of Economic Research & Business Administration, 2017)
Regulatory and stimulating function of taxes has gained the growing importance of tax policy in the current economic conditions. One of the main tools of tax system is the tax administration, so in order to improve the tax system in a new direction, it is necessary to improve tax administration itself. In determining the direction of tax administration improvement, enhancing of its effectiveness should be considered. The President of the Republic of Kazakhstan in his message requires improving tax administration mechanisms, primarily by focusing on value-added tax. The question of raising the tax administration improvement is relevant, because the main purpose of the tax administration is to ensure tax revenues on the basis of the taxation principles through an optimal combination of tax regulation methods, tax planning and tax control. The result of the tax administration efficiency is the timely and full payment of all levels’ taxes. The article deals with the factors influencing the efficiency of tax administration, and there are given some recommendations to improve the tax administration efficiency.